The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1177/1367006909356650
|View full text |Cite
|
Sign up to set email alerts
|

The phonological development of a trilingual child: Facts and factors

Abstract: This article investigates the early phonological development of a trilingual child who is acquiring Spanish, Mandarin and Taiwanese simultaneously. By examining the natural speech data recorded between the age of 1;3 and 2;0, the article reports the age of emergence and stabilization of the vowels and consonants, speech accuracy and phonological error patterns in each language. The data show that by the age of two the child is able to produce most of the vowels in the three languages. However, there are cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The question of how this comparatively limited input affects trilingual children's language development—as investigated for bilinguals when compared to monolinguals—has also been addressed in the recent literature on early trilingual acquisition. Given that the relative amount of input was not directly reflected in the relative rate of acquisition in the three languages acquired by the child in their study, Yang and Zhu (2010) noted that the relationship between amount of input and rate of acquisition is clearly not a direct one. Furthermore, given that the child's development was very much like that of monolingual children with respect to age of acquisition, rate of acquisition, and error patterns, Yang and Zhu stressed that the inevitable reduction in input for trilingual children does necessarily lead to slower acquisition.…”
Section: Characteristics Of Multilingual First Language Acquisitionmentioning
confidence: 86%
See 1 more Smart Citation
“…The question of how this comparatively limited input affects trilingual children's language development—as investigated for bilinguals when compared to monolinguals—has also been addressed in the recent literature on early trilingual acquisition. Given that the relative amount of input was not directly reflected in the relative rate of acquisition in the three languages acquired by the child in their study, Yang and Zhu (2010) noted that the relationship between amount of input and rate of acquisition is clearly not a direct one. Furthermore, given that the child's development was very much like that of monolingual children with respect to age of acquisition, rate of acquisition, and error patterns, Yang and Zhu stressed that the inevitable reduction in input for trilingual children does necessarily lead to slower acquisition.…”
Section: Characteristics Of Multilingual First Language Acquisitionmentioning
confidence: 86%
“…Montanari (2011) suggested that this may have been due to heightened sensitivity to language and its properties as a result of early multilingual exposure. In a study on the phonological development of a trilingual Spanish-Mandarin-Taiwanese child, Yang and Zhu (2010) also observed early differentiation as evidenced by different rates of acquisition in the three languages, sometimes for the same phoneme.…”
Section: Characteristics Of Multilingual First Language Acquisitionmentioning
confidence: 96%
“…Many other studies on bilingual phonological development have reported instances of interference (e.g. Fabiano & Goldstein, 2005; Yang & Hua, 2010). The overall incidence of interference in these studies is low, however.…”
Section: Introductionmentioning
confidence: 97%
“…As such, children's ability to convey ideas through the printed word is highly emphasized as their success as literacy learners is contingent on their ability to read and write. As early as preschool, young children are building their repertoire of print knowledge and are using emergent writing in the form of drawing, scribbles, letter strings and invented spelling that reflect phonetic principles as part of their transition to conventional forms (Sulzby 1992;Al-Momani et al 2010;Arikan and Taraf 2010;Wedin 2010;Yang and Hua 2010;Al-Mansour and Al-Shorman 2011;Doyle 2013;Lucas et al 2020). In this study, the emergent literacy theoretical constructs are important considering that the participant children had had no previous contact with the foreign language, and as such, the constructs to bear in mind needed to consider how literacy develops both in the native and in the foreign language.…”
Section: Motivation For Developing Readingmentioning
confidence: 99%